Case Report: Unilateral Incompletely Duplicated Ureter without any Accessory Renal Artery - Fateme Tahmasebi; Shirin Barati; Zohreh Mazaheri (Negah Institute for Scientific Communication, 2015)
There are often duplicated ureter with types of congenital anomalies and associated clinical complications. The unilateral duplicated ureter was observed as an incidence result in usual dissection. During routine dissection of the body of an adult male with middle-aged 40-50 year old, the duality of unilateral incompletely ureter was seen in above. Two branches of ureter are coalesce in 7 cm distally hilum of kidney and form a unit ureter. Right kidney and ureter were entirely normal. This variation was accruing because ureter bud split incompletely during embryogenesis. Kidney with bifid ureter forms a clear diagnosis of renal failure. These anatomical differences may exhibit pathological obstruction urinary tract and should be considered in endourological method. Awareness of relationship between renal arteries and collecting systems for applications is necessary and vital in endourological procedures and renal surgeries.